Mathematics Operation Card (MOC): Mathematics Operating Number Educational Game Cards for Elementary School Students - Faizah, Hanim; Sulistyaningtyas, Annisa Dwi (Universitas Muhammadiyah Sumatera Utara (UMSU), 2024)
Mathematics is a subject with very abstract material, so the existence of learning media is very necessary. The purpose of this research is to develop an educative game card learning media